2004
DOI: 10.1016/s0092-8674(04)00205-3
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Distinct Regulation of Yeast TATA Box-Containing Genes

Abstract: Despite being one of the first eukaryotic transcriptional regulatory elements identified, the sequence of a native TATA box and its significance remain elusive. Applying criteria associated with TATA boxes we queried several Saccharomyces genomes and arrived at the consensus TATA(A/T)A(A/T)(A/G). Approximately 20% of yeast genes contain a TATA box. Strikingly, TATA box-containing genes are associated with responses to stress, are highly regulated, and preferentially utilize SAGA rather than TFIID when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

50
746
2
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 601 publications
(807 citation statements)
references
References 57 publications
50
746
2
9
Order By: Relevance
“…These preset promoters tend to be underrepresented for TATA boxes and tend to have a strong nucleosome-depleted region at a stereotypical position relative to the transcriptional start site, a promoter architecture that has been termed "type II" (Field et al, 2008). Previous work has characterized TATA-less promoters as enriched in constitutively expressed housekeeping genes (Basehoar et al, 2004), but the work reported here clearly demonstrates that individual TATA-less preset promoters are capable of dramatic gene expression changes.…”
Section: Preset Promotersmentioning
confidence: 67%
See 3 more Smart Citations
“…These preset promoters tend to be underrepresented for TATA boxes and tend to have a strong nucleosome-depleted region at a stereotypical position relative to the transcriptional start site, a promoter architecture that has been termed "type II" (Field et al, 2008). Previous work has characterized TATA-less promoters as enriched in constitutively expressed housekeeping genes (Basehoar et al, 2004), but the work reported here clearly demonstrates that individual TATA-less preset promoters are capable of dramatic gene expression changes.…”
Section: Preset Promotersmentioning
confidence: 67%
“…We observed that genes containing TATA boxes, which constitute ϳ20% of all genes in yeast (Basehoar et al, 2004), were unusual in several respects. First, as noted previously (Ioshikhes et al, 2006;Albert et al, 2007;Mavrich et al, 2008), we found that, although the 5Ј NDRs in non-TATA containing promoters were all 200 base pairs wide and stereotypically centered 100 base pairs upstream of the TSS, the NDRs in promoters with TATA boxes were of the same size as those at non-TATA promoters but were dispersed over a much wider region, with each gene containing an individually positioned NDR.…”
Section: Promoters Containing Tata Boxes Are More Likely To Undergo Nmentioning
confidence: 90%
See 2 more Smart Citations
“…Another possibility for a characteristic of Tup1-controlled promoters that could influence which repression mechanisms are important at a particular gene is the composition of the general transcriptional machinery regulating expression at that promoter. For example, Basehoar et al (2004) and Huisinga and Pugh (2004) identified a set of genes (ϳ10% of the genome) whose regulation is dominated by the SAGA complex rather than the TFIID complex and showed that Tup1-controlled genes disproportionately fall into this category. However, all five subclasses of Tup1-repressed genes we describe in this article exhibit this same propensity for SAGA-dominated transcriptional regulation, so although inclusion in this group does seem to be a characteristic of Tup1-repressed genes, it does not seem to dictate the influence of a particular repression mechanism.…”
mentioning
confidence: 99%